Restore. Recycle. Repurpose. {create a beautiful home} - Florke, Randy; Becker, Nancy J. [ (Nancy Jane)] , 1956- (New York : Hearst Books, 2010)
"Country Living contributing editor Randy Florke shows how to decorate and renovate a home inexpensively with repurposed, restored, and recycled materials. Providing inspiration and practical information, he perfectly captures why sustainable living is important and reveals how everyone can create a home that's a harmonious with the environment as it is beautiful. What's more, 'Restore. Recycle. Repurpose.' explains how to do it without buying costly materials from far-flung places or throwing out what you already have. Room by room, Florke presents ideas, examples, and resources that are "shades of green." His approach begins with a major focus for each room, such as vanities, sinks, and tubs in the bathroom. Sharing his flea market and thrift shopping skills as well as some savvy wisdom inspired by his grandmother, Florke will help you create a welcoming, lovely, earth-friendly de?cor--without spending a fortune"--P. [2] of cover